Gastroprotective effect of mature silkworm, Bombyx mori against ethanol-induced gastric mucosal injuries in rats. (December 2017) - Yun, Sun-Mi; Cho, Jae-Min; Hong, Kyung-Sook; Lee, Da-Young; Ji, Sang-Deok; Son, Jong-Gon; Kim, Eun-Hee
Highlights: SMSP has the enriched nutrients including high contents of amino acid compositions. SMSP shows gastroprotective effect against ethanol-induced gastric ulcer. SMSP preserves intact mucous layer and total antioxidant capacity. SMSP inhibits the recruitment of immune cells in ethanol-induced gastric lesion. SMSP decreases pro-inflammatory signaling induced by ethanol administration. Abstract: Gastric ulcer is a clinical condition characterized by ulceration of the surface of the gastric mucosa. Alcohol consumption has been identified as a major cause of gastric ulceration. The silkworm, Bombyx mori, produces diverse functional materials including silk proteins. Here, we evaluated whether Steamed and freeze-dried Mature Silkworm larval Powder (SMSP) can prevent ethanol-induced gastric injury in rats. Sprague-Dawley rats pretreated with SMSP (0.1 or 1 g/kg body weight) or normal diet (AIN-76A) were subjected to intragastric administration of absolute ethanol (3 g/kg body weight, 3 h). Pretreatment with SMSP significantly prevented ethanol-induced gastric mucosal ulceration and hemorrhagic injury, by which improved the total antioxidant capacity and mucus secretion and suppressed the pro-inflammatory responses through inhibiting the recruitment of immune cells. SMSP exerted protective effects in ethanol-induced gastritis via the regulation of anti-oxidative and pro-inflammatory signaling pathway, suggesting SMSP could be anticipating remedy for the treatment of ethanol-induced gastric injury.